Change in left atrioventricular coupling index to predict incident atrial fibrillation: the multi-ethnic study of atherosclerosis (MESA). (13th July 2021) - Pezel, T; Ambale Venkatesh, B; Quinaglia, T; Heckbert, S; Kato, YOKO; De Vasconcellos, H; Wu, C; Post, W; Henry, P; Bluemke, D; Lima, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Left atrial (LA) and left ventricular (LV) structural and functional parameters have independent prognostic values as predictors of atrial fibrillation (AF). PURPOSE: Due to the intrinsic physiological relationship between LA and LV, we sought to investigate the prognostic value of a left atrioventricular coupling index (LACI) as well as change in LACI to predict incident AF in a multi-ethnic population. METHODS: In the Multi-Ethnic Study of Atherosclerosis (MESA), 1, 911 study participants, free of clinically recognized AF and cardiovascular disease at baseline, had LACI assessed with CMR imaging at baseline (Exam 1, 2000–2002), and ten years later (Exam 5, 2010–2012). LACI was defined as the ratio of LA to LV end-diastolic volumes. Univariable and multivariable Cox proportional hazard models were used to evaluate the associations of LACI and average annualized change in LACI (ΔLACI) with incident AF. RESULTS: Among the 1, 911 participants (mean age 59 ± 9 years and 47.5% male participants), 87 incident AF events occurred over 3.9 ±0.9 years following the second imaging (Exam 5). After adjustment for traditional risk factors, greater LACI and ΔLACI were independently associated with AF (HR 1.69, 95% CI [1.46-1.96] and HR 1.71, 95% CI [1.50-1.94], respectively; both p < 0.0001). Adjusted models for LACI and ΔLACI showed significant improvement in model discrimination compared to currently used AF risk score model for predicting AF incidence (C-statistic: 0.78 vs. 0.74, and C-statistic: 0.80 vs. 0.74, respectively). The LACI and ΔLACI also showed superior discrimination performance for AF compared to the multivariable model including CHARGE-AF score, and individual LA or LV parameters. CONCLUSIONS: Atrioventricular coupling (LACI) and coupling change (ΔLACI) are strong predictors for AF incidence in a multi-ethnic population. Both have incremental prognostic value for predicting AF over traditional risk factors, and superior discrimination power compared to the CHARGE-AF score and to individual LA or LV parameters.